NK Cell-Based Immunotherapy in Renal Cell Carcinoma - Terrén, Iñigo (Cancers (Basel), 2020)
Natural killer (NK) cells are cytotoxic lymphocytes that are able to kill tumor cells without prior sensitization. It has been shown that NK cells play a pivotal role in a variety of cancers, highlighting their relevance in tumor immunosurveillance. NK cell infiltration has been reported in renal cell carcinoma (RCC), the most frequent kidney cancer in adults, and their presence has been associated with patients’ survival. However, the role of NK cells in this disease is not yet fully understood. In this review, we summarize the biology of NK cells and the mechanisms through which they are able to recognize and kill tumor cells. Furthermore, we discuss the role that NK cells play in renal cell carcinoma, and review current strategies that are being used to boost and exploit their cytotoxic capabilities.